Concept of Spectrum Disorder in Psychiatry - Kukreti, Prerna; Kumar, Prerak; Mathur, Harita; Saurabh; Kataria, Dinesh (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2020)
Classification of mental disorders is a great tool to communicate amongst researchers, clinicians, epidemiologist as well as policy makers. Psychiatry nosology has been evolving with the advancement of scientific knowledge. Many approaches are used to classify the disorders ranging from categorical to dimensional to hybrid approaches. Categorical approach is helpful in delineating the prototype of disorder but spectrum concept helps in understanding the subthreshold symptoms, heterogeneity in presentation of same disorder and comorbidity across disorders. No system of nosology can be perfect until precise and accurate cause of mental illness will be known, but spectrum approach may hold the promise for being more accurate, heuristic and holistic. How to cite this article: Kukreti P, Kumar P, Mathur H, Saurabh, Kataria D. Concept of Spectrum Disorder in Psychiatry. J Adv Res Psychol Psychother 2019; 2(3&4): 29-34. DOI: https://doi.org/10.24321/2581.5822.201913